Shape Memory Polymers fundamentals, advances and applications - Hu, Jinlian (Smithers Rapra, 2014)
Shape-memory polymers (SMP) are a unique branch of the smart materials family which are capable of changing shape on-demand upon exposure to external stimulus. The discovery of SMP made a significant breakthrough in the developments of novel smart materials for a variety of engineering applications, superseded the traditional materials, and also influenced the current methods of product designing. This book provides the latest advanced information of on-going research domains of SMP. This will certainly enlighten the reader to the achievements and tremendous potentials of SMP. The basic fundam.
Keywords: Shape memory polymers.; Polymeric composites.; Polymers.; Shape memory effect.; Smart materials.; elektronické knihy; electronic books